The Influence Of Competence and Compensation On The Performance Of Army Polytechnic Teaching Staff: Mediated By Work Motivation - Rachmat Setiawibawa (International Journal of Management Research and Economics, 2025)
This study aims to examine the influence of skills and rewards on the job performance of teaching staff at the Army Polytechnic Institute, considering the role of job motivation. The study population consists of 63 teaching staff members at the Army Polytechnic Institute, with samples selected using a saturated sampling technique. Data were analyzed through path analysis. The findings indicate that skills, rewards, job motivation, and job performance of teaching staff are at a good level. Skills and rewards directly contribute positively to job motivation and job performance. Moreover, job motivation also has a significant direct impact on job performance. The mediating results show that skills and rewards, through job motivation, indirectly influence the job performance of teaching staff at the Army Polytechnic Institute.